О кручении предварительно напряженного материала с двумя параллельными соосными трещинами - Богданов, В.Л. (Видавничий дім "Академперіодика" НАН України, 2008)
An axisymmetric problem on two parallel coaxial cracks of torsion in an infinite material with initial stresses acting along cracks is investigated by use of the approaches of the three-dimensional linearized mechanics of solids. Numerical results are obtained for highly elastic materials with Bartenev–Khazanovich and Treloar elastic potentials. The dependence of the stress intensity factors on the initial stresses and geometric parameters of the problem is analyzed.